Save Nature to Survive N 11(1): 647-650, 2016 (Supplement on Agronomy) www.thebioscan.in 647 DRYING CHARACTERISTICS OF DIFFERENT CORIANDER (CORIANDRUM SATIVUM L.) VARIETIES ARIETIES - ONTAGODI, TEJASHRI; GOUDA PATIL, D SHANKAR (The Bioscan, 2016)
A lab experiment was conducted to know the effect of drying on colour and sensory characteristics of different varieties of coriander herbage during 2012-13 at department of plantation, spices, medicinal and aromatic crops, Kittur Rani Channamma College of Horticulture, Arabhavi (Karnataka). The experiment was laid out in completely randomized design with three replications and thirteen treatments. Studies on the drying characteristics of different coriander varieties revealed that the maximum drying ratio and rehydration ratio were recorded in Rcr480 (5.42) & DWD-3 (4.23) respectively. The variety RCr-446 was only towards the lightness (58.07). The mean values of L* decreased from fresh herbage (40.09) to dried herbage (36.67). The mean values for redness (a*) decreased from (-7.57) to (-2.26). The b* value was towards the yellowness for both fresh and dried herbage. The highest score for flavor and aroma was observed in DWD-3 (7.97) and highest score for colour (8.00) and overall acceptability (7.77) was observed in RCr-435.